Fiscal Policy And Economic Growth: And Empirical Evidence In Malaysia And Indonesia - Jaka Sriyana (Economic Journal of Emerging Markets, 2002)
Since the financial crisis occurred in the mid of 1997, generally the government of Asian countries have difficulties in supporting their economic growth. This paper attempts to analyze the relationship between fiscal variables, including government expenditure, revenue and output in Malaysia and Indonesia. The relationship between government expenditure and revenue will be tested by co integration and causality test, meanwhile the effect of gov-ernment expenditure and revenue on output will be tested using Vector Error Correction Model (VECM). The result shows that there are strongly long run relationship between fiscal variables and output in these two countries. More active fiscal policy is recommended in Malaysia, meanwhile a better fiscal management must be applied in Indonesia.Key words: Co integration, Causality, Error Correction Model, Fiscal policy.